Ricerche archeologiche a Sant'Andrea di Loppio (Trento, Italia) : il castrum tardoantico-altomedievale - Maurina, Barbara (Archaeopress Publishing Ltd, 2016)
The island of Sant' Andrea, situated on the road that since ancient times has linked the Adige Valley with the Lake Garda, is now little more than a small hump on the edge of a vast marshy basin. Excavations reveal a multi-layered archeological site with finds ranging from the prehistoric age right through to the First World War.